Psychological intervention programs to address partner violence: Systematic review in the period 2010 to 2020 in four Ibero-American countries - Duque Moreno, Jacive; Rueda Castillo, Lizeth Paola; Pabón Poches, Daysy Katherine; Guzman Pacheco, Juan Felipe; Acevedo Carvajal , Claudia Patricia (Pensando Psicología, 2025)
Intimate partner violence is a social and public health issue that requires intervention through strategies aimed at increasing the effectiveness of psychological treatment, involving both the victim and the perpetrator. This research aimed to analyze documented psychological intervention programs for intimate partner violence in Spain, Chile, Mexico, and Colombia from 2010 to 2022. This study is expected to contribute to the development of effective intervention proposals for this issue. The method implemented was a systematic review of the scientific literature with a descriptive design. The document search was conducted using keywords such as “intervention,” “victims,” and “intimate partner violence perpetrators,” extracted from reliable databases. Through Health Sciences Descriptors (DeCS), such as “intimate partner violence,” “intervention programs,” “perpetrators,” and “victims,” descriptive records were created, allowing the analysis of information at both the national and international levels. The analysis focused on the methodology of the 21 programs that met the criteria of language (Spanish and English), country of origin, and a specific description of the methodology and effective results. The results showed that victim programs focus on reducing symptoms of post-traumatic stress disorder (PTSD), while perpetrator programs aim to modify maladaptive behaviors, with the cognitive-behavioral model being the most commonly implemented, and the use of guidelines by Spanish authors prevalent in the Latin American context.